Correlation analyses between volatiles and glucosinolates show no evidence for chemical defense signaling in Brassica rapa - Schiestl, Florian P. (Frontiers in Ecology and Evolution, 2014)
Positive correlations between volatile organic compounds (VOCs) and defense chemicals indicate signaling of defense status. Such aposematic signaling has been hypothesized to be widespread in plants, however, it has up to now only been shown for visual signals. Correlations between identical compounds in different plant tissues, on the other hand, can be informative about the (co-)regulation of their biosynthesis or emission. Here I use Brassica rapa to investigate 1) correlations between identical metabolites (volatiles, glucosinolates) in leaf and flower tissue, and 2) correlations between volatiles and glucosinolates in the same plant organs (flowers and leaves). Whereas the amounts of many glucosinolates were positively correlated in leaves and flower tissue, identical leaf and floral VOCs showed no such correlations, indicating independent regulation of emission. None of the leaf or flower volatiles showed positive correlations with the two major glucosinolates (gluconapin, glucobrassicanapin) or the sum of all glucosinolates in either leaves or flowers. Some VOCs, however, showed positive correlations with minor glucosinolates which, however, represented less than one percent of the total amounts of glucosinolates. Some leaf monoterpenes showed negative associations with gluconapin. The lack of consistent positive correlations between VOCs and major defense compounds suggests that plants do not chemically signal their defense status. This could be adaptive as it may avoid eavesdropping by specialist herbivores to locate their host plants. Negative correlations likely indicate chemical trade-offs in the synthesis of secondary metabolites.